Technology alliances in emerging economies: persistence and interrelation in European firms' alliance formation. (22nd July 2013) - Jacob, Jojo; Belderbos, René; Gilsing, Victor
Abstract : We analyse the patterns and determinants of technology alliance formation with partner firms from emerging economies with a focus on European firms' alliance strategies. We examine to what extent European firms' alliance formation with partners based in emerging economies is persistent – that is, to what extent prior collaborative experience determines new alliance formation – and we compare this pattern with alliance formation with developed country partners. Second, we examine to what extent prior engagement in international alliances with partners from developed countries increases the propensity to form technology alliances with partners based in emerging economies, and vice versa (interrelation). We find that both persistence and interrelation effects are present, and that they are generally not weaker for emerging economy alliances. Alliance formation with Indian and Chinese firms is significantly more likely if firms have prior alliance experience with Japanese firms. The findings suggest that building on their prior international alliance experience firms extend their alliance portfolios across both developed and emerging economies, increasing the geographical diversity of their alliance portfolios.